Towards an Agenda for Post‐carbon Cities: Lessons from Lilac, the UK's First Ecological, Affordable Cohousing Community. (25th March 2013) - Chatterton, Paul
Abstract This article explores an agenda towards post‐carbon cities, extending and deepening established debates around low‐carbon, sustainable cities in the process. The label post‐carbon builds upon issues beyond those of greenhouse gas (GHG) emissions, energy conservation and climate change, adding a broader set of concerns, including economic justice, behaviour change, wellbeing, land ownership, the role of capital and the state, and community self‐management. The article draws upon a case study of an embryonic post‐carbon initiative completed in early 2013 called Lilac. Based in Leeds, Lilac stands for Low Impact Living Affordable Community and is the first attempt to build an affordable, ecological cohousing project in the UK. Its three aspects each respond to significant challenges: low‐impact living and the challenge of post‐carbon value change; affordability and the challenge of mutualism and equality; and community and the challenge of self‐governance. I conclude the article by exploring six lessons from Lilac that tentatively outline a roadmap towards post‐carbon cities: the need for holistic approaches that deal with complex challenges, prioritizing self‐determination rather than just participation, engaging with productive political tensions, adopting a process rather than an outcomes‐based approach, developing strategy for replicability, and finally, embracing a non‐parochial approach to localities.